A novel taxonomy for facilitating in-depth comparison of continuing engineering education practices - Caratozzolo, Patricia; Smith, Christopher J. M.; Gomez, Sonia; Moris, Matías Urenda; Nørgaard, Bente; Heiß, Hans-Ulrich; Azofeifa, Jose Daniel (Frontiers in Education, 2024)
Introduction. This study addresses the urgent need for standardized frameworks in Continuing Engineering Education (CEE) to support lifelong learning in the rapidly evolving global workforce. Significant events, such as the Digital Transformation and the rise of artificial intelligence, have highlighted the demand for adaptable and diverse learning systems, especially in engineering education. On the one hand, the World Economic Forum's 2023 Future of Jobs Report predicts a transformation in 44% of workers' core skills within five years, with engineering facing substantial labor shortages. On the other hand, the Paris Agreement's call for sustainable development necessitates a workforce with skills aligned with the green transition.Methods. The research introduces an innovative framework taxonomy that categorizes and organizes CEE programs by integrating standardized terminologies. It focuses on critical elements such as resourcing, organizational models, and program development strategies to provide a comprehensive structure that supports consistency and comparability across diverse educational contexts.Results. Unlike existing models, the proposed framework enhances cross-institutional learning and dissemination of best practices. It identifies key components required for effective CEE management, filling a critical gap in the literature. The study's output is a taxonomy for discussing and comparing CEE institutional approaches and practices to advance the field and foster a global CEE community committed to excellence in engineering education. PAGE \* Arabic \* MERGEFORMAT Discussions. This study equips educators, policymakers, and industry leaders with a practical tool to design, implement, and scale CEE programs. It ultimately fosters a skilled workforce prepared to meet the challenges of future technological and sustainable transitions, supporting the development of a standardized approach to CEE.